Portfolio Optimization using the Optimized \(α\) in Renyi Entropy - Sajedi, Alireza; Yari, Gholamhossein (Communications in Mathematics and Applications, 2019)
In this paper, a new approach of portfolio optimization using Renyi entropy is presented. In the proposed method, we use Renyi Entropy as a measurement of risk by determining the minimum return. We also attempt to examine the relationship between Renyi Entropy's \(α\)-level and risk. Then, a single-objective function with penalty function approach based on Renyi Entropy-mean-semi-variance models is developed. As a result, we find the optimized \(α\) denoting the most appropriate portfolio related to the risk level denoted by the investor. Finally by providing an illustrative example, the validity of this method is checked and the conclusion is drawn.